2001
DOI: 10.1002/mde.999
|View full text |Cite
|
Sign up to set email alerts
|

Assessing self‐reported expenditures on gambling

Abstract: Estimates of the proportion of gambling revenues derived from problem gamblers represent an important element in the rational calculus of public gambling policy. However, a critical concern in calculating such estimates is the accuracy of self-reported expenditure data. In this paper, we review an emerging literature on estimating the proportion of expenditures from problem gamblers for different types of gambling, with a focus on the relationship between self-reported estimates and known spending. We then exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…Next, male legislators vote more liberally on lottery votes; this issue area includes all gambling‐related votes as well as lottery votes. Other research has found that women generally are less likely to view gambling favorably and to participate in illegal gambling (Volberg et al, :84); taken together, these findings suggest that female legislators approach this issue differently than men, even after controlling for their political beliefs.…”
Section: Resultsmentioning
confidence: 72%
“…Next, male legislators vote more liberally on lottery votes; this issue area includes all gambling‐related votes as well as lottery votes. Other research has found that women generally are less likely to view gambling favorably and to participate in illegal gambling (Volberg et al, :84); taken together, these findings suggest that female legislators approach this issue differently than men, even after controlling for their political beliefs.…”
Section: Resultsmentioning
confidence: 72%
“…blood alcohol). Consequently, measuring levels of involvement relies entirely upon self‐report methods, which have been shown to be unreliable . Although Walker et al .’s paper aims to facilitate cross‐comparability of outcomes, it does not endorse specific instruments designed to assess each domain.…”
Section: Introductionmentioning
confidence: 99%
“…Some behavioural characteristics that were used to diagnose/identify problem gambler, including chasing losses or increasing bet sizes (American Psychiatric Association, 2000;Ferris & Wynne, 2001;Lesieur & Blume, 1987), can be monitored in a manner that is more reliable than past research tools such as survey self-report data (Hodgins & Makarchuk, 2003;Volberg, Gerstein, Christiansen, & Baldridge, 2001). Osborn, Skelt, Delfabbro, Nevile, and McMillen (2007) and Schellinck and Schrans (2007) conducted major empirical studies that examined observable signs of problem gambling in gaming venues.…”
Section: Empirical Studiesmentioning
confidence: 99%